A Receiver Perspective on Knowledge Sharing Impact on Consumer–Brand Relationship in Virtual Communities - Zhang, Jiemei; Qi, Shaojing; Lyu, Bei (Frontiers in Psychology, 2021)
The virtual community offers groups of consumers a knowledge-shared platform, wherein shared brand information influences the brand cognition of others. Using stimulus–organism–response (SOR) model, this study constructs a research framework for the influence of knowledge sharing on consumer–brand relationship in virtual communities. The empirical analysis shows that knowledge-sharing quality has significant positive effects on the sense of virtual community, as does the sense of virtual community on the consumer–brand relationships. This study supports the strengthening of consumer–brand relationships and the enrichment of following research on knowledge sharing of the consumer in virtual communities. Thus, companies should encourage consumers to actively participate in brand activities and focus on the development of consumer–brand relationships during participation in brand promotion.